A Statistical Understanding of Disability in the LGBT Community - Chris R. Surfus (Statistics and Public Policy, 2023)
AbstractFor the first time ever, the United States Census Bureau began collecting data on the LGBT community with Phase 3.2 of the Household Pulse Survey. The Household Pulse Survey assesses how residents of the United States are doing during the COVID-19 pandemic. The data provided by the Household Pulse Survey Week 34 through Week 39 provides information to understand the lives of LGBT residents of the United States and how the LGBT community as a whole is doing economically. This study merges six weeks of the Household Pulse Survey, for a total of 382,908 survey responses. The sample represents a population of 250,265,449 adult residents aged 18 and older in the United States. This study provides the first nationally representative sample of residents of the United States that identify as transgender. This study specifically focuses on LGBT people with disabilities but highlights disparities facing transgender disabled U.S. adult residents. Disability is defined in the Household Pulse Survey as a severe or total impairment of those with seeing, hearing, remembering, and mobility disability types. The data indicates significant disparities for LGBT people compared to non-LGBT people, specifically in terms of economic considerations like work loss, household finances, and mental health.